2011
DOI: 10.1148/radiol.11110122
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Renal Tumors Arising in Kidney Transplants: Midterm Outcome after Percutaneous Thermal Ablation

Abstract: Purpose:To retrospectively evaluate the midterm outcome of patients treated for primary renal cell carcinomas arising in kidney transplants with minimally invasive techniques. Materials and Methods:The institutional review board of each participating institution approved this retrospective study and waived informed consent . This study was HIPAA compliant. A request for cases through the European Society of Urogenital Radiology network was made to institutions for patients who fi t the requirements outlined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…Studies have shown that CA in this subgroup represents an attractive option as the primary treatment modality or after recurrence following PN [40,41]. Another special indication for CA may include patients with a solitary or transplanted kidney, especially when presenting with recurrent disease [42,43]. The minimally invasive nature of CA, in particular the E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X percutaneous route, and maximal preservation of renal function are the cited advantages of this approach.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Studies have shown that CA in this subgroup represents an attractive option as the primary treatment modality or after recurrence following PN [40,41]. Another special indication for CA may include patients with a solitary or transplanted kidney, especially when presenting with recurrent disease [42,43]. The minimally invasive nature of CA, in particular the E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X percutaneous route, and maximal preservation of renal function are the cited advantages of this approach.…”
Section: Patient Selectionmentioning
confidence: 99%
“…[18][19][20][21] Cryoablation involves the insertion of a probe into a tumor nodule in order to administer tissue ablative freezing temperatures, which will lead to immediate disruption of the tissue structure and cellular damage. 22 The necrosis observed in the ablated lesion is mediated by mechanical disruption from crystallization, osmotic changes, and vascular stasis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were treated for small, exophytic masses consistent with current practice for native kidney tumors. Cornelius et al demonstrated robust mid-term oncologic efficacy in the largest series of allograft tumors treated by RFA (n=24) and no significant worsening of renal function (25). Our patient is, to our knowledge, the first report of large multifocal allograft RCC disease managed with RFA.…”
Section: Discussionmentioning
confidence: 54%